Proposed Design of Knowledge Based Performance Management System (KBPMS) for SME In Metal Casting Business - Ahmad Auva Nadiyyi Kaff; Dermawan Wibisono; Ima Fatima (Journal of Research in Social Science and Humanities, 2025)
PT. SPU is a private metal casting company located in the Ceper industrial area, Klaten, Central Java. The company operates a metal casting factory equipped with an Induction Melting Furnace. Their product portfolio includes a wide range of materials, such as Cast Iron, Stainless Steel, Steel, Aluminum, Brass, and various alloy metals, meeting diverse industrial demands. This study focuses on proposing a Knowledge-Based Performance Management System (KBPMS) to address the company’s operational challenges. PT. SPU faces issues like fluctuating income, reliance on conventional marketing methods, frequent product defects, project delays, and the absence of well-defined key performance indicators (KPIs). These obstacles hinder sustainable growth and operational efficiency. The KBPMS framework offers a structured approach to performance management, integrating business knowledge and systematic evaluation to overcome these issues. By establishing clear KPIs, the system ensures alignment with organizational objectives, providing tools to track progress and identify areas for improvement. Additionally, the framework promotes a culture of continuous enhancement, ensuring quality, timeliness, and customer satisfaction. Implementing KBPMS is expected to stabilize financial performance, modernize marketing, reduce defects, and improve project completion rates, ultimately fostering a more resilient and competitive organization.